Correlation Of Peak Particle Velocity During Blasting And Particle Size Distribution - Aziz, Muhammad Syamim Che (Universiti Sains Malaysia, 2017)
Fragmentation control of blasted rock can be regulated through a number of parameters, but governing factor through estimated peak particle velocity by vibration monitoring are somewhat overlooked as a significant parameter in blasting outcome. In any quarry blasting operation, monitoring of blast induced ground vibration to be under stipulated levels is very important to hinder any damage to nearby structures and protect civilian safety and lessen complaints towards the quarry work. This research is dedicated to find correlation between blast-induced ground vibrations through peak particle velocity monitoring with the wanted particle size distribution of blasted rock. Fragmentation for blasting operations have to be in line with demands and in the stated area of study the demand is to be 800 mm in size or lower. The study is done by monitoring quarry blasts using geophones and analyzing in Blastware. Site specific coefficients are obtained to enable prediction of PPV. Fragmentation analysis is done through digital image analysis, where the software Wipfrag was utilized. The establishment stating high PPV induces good fragmentation was achieved and prediction is possible.